Epidemiological study on body mass index distribution and health awareness among women at an urban tertiary care centre of north India - Datta, Kamna; Gupta, Pooja; Singh, Pushpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Obesity has become a new worldwide health problem and is gradually moving towards an epidemic. overweight and obesity implies an abnormal excessive fat accumulation that poses health risk. According to National Family Health Survey-4, prevalence of obesity has doubled in country over the last decade. Asian Indians stand at higher risk for development of obesity related non-communicable diseases at lower body mass index levels. Methods: It was an observational interpretive study carried on 1000 randomly selected women over 3 months in a tertiary center of urban northern India. BMI was obtained by dividing weight in kilograms and height in meters squares. Patients were enquired about any menstrual complains, known comorbidities, awareness of obesity in terms of its cause and effects, about weight reduction and benefits of exercise and its practice and details noted in a preformed performa. No prior intervention or health education was given to avoid bias. Results: Out of 1000 women, mean BMI was found to be 31.85±8.85kg/m2. BMI classification (Asian standards) stated that 8.1% were overweight and 78% of patients were pre obese and obese (maximum in age of 21-40 years). Menstrual complaints were present among 39% of overweight and obese groups. Among comorbidities, hypothyroidism was found to be maximum being 9.5% in the obese group, followed by hypertension and diabetes mellitus. Only 26.3% of obese women were aware of the factors causing obesity. Knowledge of exercise benefits was grossly limited, with only one fourth of the pre obese and obese population being aware of it. Conclusions: Rising obesity in Indian women needs measures for prevention. Though there is knowledge of the cure among Indian females but there is limited ability to implement the same. Health education of women regarding obesity related comorbidities along with the benefits of weight loss with exercises should be promoted strongly.